Nigerian SMEs: Commitment and loyalty to their banks. Issue 4 (December 2016) - Ojeme, Mark; Robson, Andrew; Coates, Nigel
Abstract Commitment has a crucial role to play in underpinning long-term business relationships, and as such, is well established in the related academic literature. Limited research does, however, exist pertaining to the specific relationships between SMEs and their banks. This paper presents and assesses commitment relationship framework that seeks to evaluate such relationships. Various validated scale-sets from the existing studies are combined here to assess commitment, advocacy and repurchase intention. Data were collected from 199 SMEs via interviews with owners or senior (financial) managers. Their assessment involved exploratory factor analysis to determine underlying data structure, with internal reliability assessment of the identified factors. Commitment is established around two components; affective and calculative, whilst advocacy and repurchase intention converge into a single behavioural intentions factor. The two-dimensional presentation of commitment and behavioural intentions are also distinct. Originality lies in the validation of commitment and behavioural intention constructs within this specific business arena and geographical location, as well as showcasing research that involves engagement with smaller organisations rather than their larger counterparts in the consideration of bank performance.